Revisiting the Anomalous Relationship between Inflation and Real Estate Investment Trust Returns in Presence of Structural Breaks: Empirical Evidence from the USA and the UK - Das, Mahamitra; Sarkar, Nityananda (International Journal of Economics and Financial Issues, 2020)
In this paper we have re-investigated the frequently observed anomalous negative relationship between inflation and REIT returns for two most important economies viz., the USA and the UK by addressing two aspects of misspecification: inappropriate functional form and omission of relevant variable. We have found that the anomalous relationship between REIT and inflation appear to proxy for the significant effect of relative price variability on REIT returns in both the countries. Further, it is evidenced that the effect of relative price variability on real estate investment trust (REIT) returns is not stable over time in case of the USA while in the UK there is no structural change in the relationship. Keywords: REITs; Relative price variability; Inflation; Structural breaks. JEL Classifications: E31; G12; R3. DOI: https://doi.org/10.32479/ijefi.9013